Association of inorganic species release with sugar recovery during wood hydrothermal processing - Liaw, Sui Boon; Yu, Yun; Wu, Hongwei (2016)
© 2015 Elsevier Ltd. All rights reserved. Over 90% of the inherent Mg and Ca in wood can be released during wood hydrothermal processing in a semi-continuous flow reactor at 10 MPa and 150 °C. An increase in temperature to 180 °C results in rapid release of Mg and Ca, but a further increase in temperature has little effect. The release of Mg and Ca is associated with the conversion of organic matter during hydrothermal processing. In particular, the release of water-insoluble Mg and Ca correlates well with the arabinose recovery, suggesting that these species are bound to carboxylic acid functional group on hemicellulose side chains and their release requires the cleavage of these side chains.